Optimizing Hydrogenation Production via Recycle Loop in Aspen HYSYS Simulated Water Gas Shift Reaction: Kinetic and Thermodynamic Analysis - Christopher Beryl Nugraha Adi; Thania Nurjulianti Agus; Naurah Dwicalista Hanifah; Muhammad Ridho; Virnanda Namia Leonica (Journal of Chemical Engineering Research Progress, 2026)
Hydrogen production via the water–gas shift (WGS) reaction plays a central role in modern energy systems, where maximizing the conversion of carbon monoxide (CO) into hydrogen (H₂) and carbon dioxide (CO₂) is essential for process efficiency. This study develops a detailed Aspen HYSYS process model to simulate the WGS reaction in an equilibrium reactor, emphasizing process intensification through a recycle loop. The baseline configuration achieves 80.07% CO conversion at 469.6 °C, whereas introducing a recycle stream elevates conversion to 99.90% at a significantly lower reactor temperature of −91.91 °C. This enhancement is accompanied by an increase in hydrogen production from 44.05 kmol/h to 55.01 kmol/h. The recycle stream rich in CO₂ at low temperature functions as an in situ cooling mechanism, shifting the exothermic equilibrium toward greater H₂ formation in accordance with Le Chatelier’s principle. This behavior also increases the thermodynamic equilibrium constant, reinforcing the conversion improvement. Kinetic evaluation relies on Gibbs free energy minimization to determine equilibrium compositions, while thermodynamic analysis underscores the dominant influence of temperature on reaction performance. The findings are consistent with trends reported in the literature and carry meaningful industrial implications. By achieving near-complete CO conversion without additional catalysts or membrane technologies, the recycle strategy reduces reliance on downstream purification units such as PSA and enhances overall energy efficiency through process intensification. Copyright © 2026 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).